Human Vulnerability and Natural Slavery in The Faerie Queene. (2nd January 2022) - Griswold, Jeffrey B.
ABSTRACT: This article traces Aristotelian ideas about natural slavery through Book VI of Edmund Spenser's The Faerie Queene . By putting the Salvage Man episode in conversation with Louis Le Roy's commentary on the Politics, I demonstrate that the poem naturalizes the enslavement of extra-European peoples. This reading reconsiders analysis of the Salvage Man as a figure of savage assimilation. Rather than become civil himself, the Salvage Man is shown to be congenitally predisposed to serving others who are physiologically more vulnerable and in need of his labor. I argue that Spenser's depictions of these physically weak characters racialize the need to be served by others. Vulnerability is here a racial category used to naturalize the enslavement of bodies imagined to be stronger, harder, and less than human in their resilience. The article ends by rereading the Salvage Nation episode in light of the Salvage Man's representation of natural slavery, showing that these two encounters align human vulnerability and racial whiteness. Taken together, these episodes suggest that to be human is to be feeble, White, and in need of enslaved bodies.